Willingness to receive a COVID-19 booster vaccine and its associated factors among adults with chronic disease: a cross-sectional study in Putrajaya, Malaysia - Abdullah, Noor Shahira; Ching, Siew Mooi; Ali, Hanifatiyah (Academy of Family Physicians of Malaysia, 2023)
Introduction: Booster vaccination has been shown to reduce transmission and serious infection with COVID-19. This study examined the willingness to receive a COVID-19 booster vaccine and its associated factors among high-risk patients at Klinik Kesihatan Putrajaya Presint 9. Methods: A cross-sectional study was conducted among patients aged ≥18 years attending Klinik Kesihatan Putrajaya Presint 9 with a high risk of contracting COVID-19 recruited via systematic random sampling. Data were collected using a self-administered questionnaire. A multiple logistic regression analysis was performed to identify the associated factors. Results: The response rate for this study was 97.4% (N=489). The median patient age was 55 years. Approximately 51.7% were men, and 90.4% were Malays. Approximately 81.2% were willing to receive a COVID-19 booster vaccine. The patients who perceived COVID-19 as a serious illness (Adjusted Odd Ratio, AOR=2.414), those who perceived COVID-19 booster vaccines as beneficial (AOR=7.796), those who disagreed that COVID-19 booster vaccines have many side effects (AOR=3.266), those who had no doubt about the content of COVID-19 vaccines (AOR=2.649) and those who were employed (AOR=2.559) and retired (AOR=2.937) were more likely to be willing to receive a booster vaccine than those who were unemployed and those who did not have close friends or family members who contracted severe COVID-19 (AOR=2.006). Conclusion: The majority of the participants were willing to receive a COVID-19 booster vaccine. Healthcare authorities should take initiatives to design targeted public intervention programmes to increase the willingness for COVID-19 booster vaccination.